Changing Time and Options in Foreign Language Teaching of ELT Teachers in Northern Cyprus - Ayman Riheel Alnaas Taha; Sarah Mohammed Alsanousi Alssayah Ahmed; Sajjad Hussain (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2022)
We live in the world where English language has become the most international language for communication among the other foreign languages. English just as the other languages has been used as a medium of communication for diplomatic relationship, administrative affairs, employment, commerce, or trade and above all for education. However, policies regarding foreign language teaching teachers in Northern Cyprus must be reviewed to provide immense opportunities to enhance language competence of both language teachers and learners. In this sense, foreign language teaching and learning policy in ELT as well as other foreign languages must be well taught and successfully integrated into school systems and societies. Hence, the open-ended questions have been administered to six (6) foreign language teachers to elicit more detailed responses concerning teachers’ perception on changing time and options in teaching industry. The findings reveal how significant it is to introduce positive changes in foreign language teaching. The study suggests to be circumspect in the implementation of language policies and classroom activities regarding foreign language teaching and learning in order to prevent negative influences on both the teachers’ and the learners’ first language, ethnicity or culture.